1994
DOI: 10.1111/j.1439-0418.1994.tb00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Pheidoleants as potential biological control agents of the boll weevil,Anthonomus grandis(Col., Curculionidae), in Southeast Brazil

Abstract: This study evaluates the potential of ants as natural biological control agents of the boll weevil (Anthonomus grandis), during the between‐season period, in South‐east Brazil. Active adults of Anthonomus were experimentally distributed on the ground of the cotton field. Results show that 20% of the adult Anthonomus are attacked and removed by foraging ants. The native ant Pheidole oliveirai was by far the most efficient predator, accounting for 94 % of the predation on Anthonomus. Recruited workers of P. oliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Many Pheidole species are predators of eggs and immature stages of insects and have been reported as effi cient agents for biological control of pests in several crops (Way & Khoo 1992, Fernandes et al 1994. However, the presence of Solenopsis invicta (Bruen) in agroecosystems has been reported as dubious, because this ant is an important predator of pests, but also has harmful effects on populations of natural enemies of several insect pests (Way & Khoo 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Pheidole species are predators of eggs and immature stages of insects and have been reported as effi cient agents for biological control of pests in several crops (Way & Khoo 1992, Fernandes et al 1994. However, the presence of Solenopsis invicta (Bruen) in agroecosystems has been reported as dubious, because this ant is an important predator of pests, but also has harmful effects on populations of natural enemies of several insect pests (Way & Khoo 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, studies of ant communities in agroecosystems have contributed to the knowledge of the infl uence of agriculture activities on natural environments (Castro & Queiroz 1987, Lobry de Bruyn 1999, Fernandes et al 2000. Studies of ant communities in agroecosystems have also helped to identify ant species with potential for biological control in several types of crops (Castro & Queiroz 1987, Carroll & Rish 1990, Fernandes et al 1994. Furthermore, several authors consider ants as ecosystem engineers, because ants respond to changes in physical and chemical properties of the soil, increasing its drainage, aeration and nutrient quantity, which contribute to agricultural practices of low ecological impact (Brussaard et al 1997, Folgarait 1998, Lobry de Bruyn 1999.…”
Section: Qual é O Efeito Do Uso Do Solo Sobre As Comunidades De Formimentioning
confidence: 99%
“…According to Hölldobler and Wilson (1990), this group is the largest subfamily of Formicidae in number of species and variety of food and nesting habits, with wide adaptation to disturbed environments. Furthermore, many authors have shown that most Myrmicinae species are aggressive and they have efficient and massive recruitment, being of ten sampled in agrosystems (Castro & Queiroz, 1987;Perfecto, 1991;Lange et al, 2008;Falcão et al,2015).They are considered to be effective agents in the biological control of pests in crops (see Fernandes et al,1994Fernandes et al, , 2012.…”
Section: Community Compositionmentioning
confidence: 99%
“…Many investigations were undertaken to study the population behavior, biological responses and other ecological aspects of this curculionid pest in this new habitat, to establish IPM strategies for its control (Fuchs & England, 1989;Gutierrez et al, 1991;Gabriel et al, 1992;Pierozzi Jr. & Habib, 1992a, 1992b, 1993a, 1993bRamalho & Silva, 1993;Fernandes et al, 1994;Araujo & Azevedo, 1997). Many ecological and behavioral differences were observed among boll weevil populations in their new environment in comparison to other cotton agroecosystems, mainly of the U.S.A. (Pierozzi Jr., 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, some weevils would survive in old cotton stalks. Some authors consider the possibility that a part of A. grandis population does not accomplish the diapause process (Palmer & Cate 1992;Fernandes et al, 1994).…”
Section: Introductionmentioning
confidence: 99%